Dynamic Office Environments Improve Brain Activity and Attentional Performance Mediated by Increased Motor Activity - Henz, Diana; Schöllhorn, Wolfgang I. (Frontiers in Human Neuroscience, 2019)
Current research demonstrates beneficial effects of physical activity on brain functions and cognitive performance. To date, less is known on the effects of movements that do not fall into the category of sports related aerobic or anaerobic exercise but involve gross motor movements. In previous studies, we found beneficial effects of dynamic working environments, i.e. environments that allow movements during cognitive task performance, on cognitive performance and the corresponding brain activity. The aim of the present study was to examine the effects of a dynamic and a static office environment on attentional and vigilance performance and on the corresponding EEG brain activation patterns. In a two-week intervention, participants worked either in a dynamic or a static office. In each intervention group, twelve subjects performed attentional and vigilance tasks. Spontaneous electroencephalographic (EEG) activity was measured on the first, and on the last experimental session continuously before, during, and immediately after each intervention session. EEG was recorded from nineteen electrodes. Results showed differences in EEG brain activity in the dynamic compared to the static office at the beginning as well as at the end of the intervention. EEG theta power was increased in the vigilance task in anterior regions, alpha power in central and parietal regions in the dynamic compared to the static office. Further, increases in beta activity in the attention and vigilance test were shown in the dynamic compared to the static office. Beta power was increased in frontal and central regions. Gamma power was increased in the d2-R test in frontal and central regions. After two weeks, the effects on brain activity increased for the attentional and the vigilance task in the dynamic office. Increased theta and alpha oscillations were obtained in anterior areas with increased activity in the beta and gamma bands in anterior and central areas in the dynamic compared to the static office. EEG oscillatory patterns indicate beneficial effects of dynamic office environments on attentional and vigilance performance that are mediated by increased motor activity. We discuss the obtained patterns of EEG oscillations in terms of the close interrelations between the attentional and the motor system.